Pelatihan kewirausahaan: Pengolahan sampah plastik menjadi produk bernilai jual bagi ibu-ibu rumah tangga dan remaja - Muhammad Rakib; Ilham Thaief; Dian Anugrah sanusi (DEDIKASI, 2019)
The partner of this Community Partnership Program (PKM) was Labakkang District Head, Pangkep Regency. The problem is: (1) the lack of public knowledge (housewives and young women) about the use of plastic waste into selling value products and (2) the lack of skills of housewives and young women in processing plastic waste into sale value products. The targets are housewives and young women. The methods used are: observation, testing, training, and evaluation. The results achieved are (1) housewives and young women have very high levels of participation in training in processing plastic waste into valuable products and (2) housewives and young women have the knowledge and skills to process plastic waste into products selling value.